Factors Causing Neonatal Death At Panembahan Senopati Bantul Hospital In 2021–2022 - Fauzul Husna; Puspitasari, Riadinata Shinta; Annisa Salsabila (Jurnal EduHealth, 2024)
Neonatal Deaths in the Special Region of Yogyakarta (DIY) in 2021 areranked 8th lowest out of 34 Provinces in Indonesia with 212 cases, (RI Ministry of Health, 2022). The objective to find out the description of neonatal mortality faktors at Panembahan Senopati Hospital, Bantul in 2021 – 2022. The method used in this research is descriptive quantitative cross-section research design with the Secondary Data Analysis (SDA) approachto medical records at Panembahan Senopati Bantul Hospital in 2021 - 2022. The sample method is a total sampling of 47 respondents. Research Results: The highest percentage of research results regarding the description of neonatal mortality faktors at Panembahan Senopati Hospital, Bantul Regency in 2021-2022, namely infants aged 0-28days, died of asphyxia asmany as 33babies (70%), gestational age of 28 mothers (60%), occupation 26 mothers (55%), Low Birth Weight 53 babies (25%), Parity 22 mothers (47%), Other Causes 18 cases (38%), Sepsis 18 babies (38%), Type of Childbirth 15 mothers (32%), Status Referral 13 cases (30%), Education 13 mothers (28%), Age 12 mothers (26%), Anemia Status 11 mothers (23%), Congenital Abnormalities 7 babies (15%), Antenatal Care Visits 4 mothers (9%), Delivery Place 2 case s(4%), Delivery Assistance 2 cases (4%), Jaundice 0 cases (0%). There are factors of neonatal death based on maternal factors, infant faktors, health service factors and other faktors at Panembahan Senopati Hospital in 2021-2022.